Design, synthesis and preliminary evaluation of 18F-labelled 1, 8-naphthyridin- and quinolin-2-one-3-carboxamide derivatives for PET imaging of CB2 cannabinoid receptor. Issue 12 (15th June 2015) - Saccomanni, Giuseppe; Pascali, Giancarlo; Carlo, Sara Del; Panetta, Daniele; De Simone, Mariarosaria; Bertini, Simone; Burchielli, Silvia; Digiacomo, Maria; Macchia, Marco; Manera, Clementina; Salvadori, Piero A.
Graphical abstract: Abstract: In the present work, we report the synthesis of new aryliodonium salts used as precursors of single-stage nucleophilic 18 F radiofluorination. The corresponding unlabelled fluorinated derivatives showed to be CB2 cannabinoid receptor specific ligands, with K i values in the low nanomolar range and high CB2/CB1 selectivity. The radiolabelled compound [ 18 F]CB91, was successfully formulated for in vivo administration, and its preliminary biodistribution was assessed with microPET/CT. This tracer presented a reasonable in vivo stability and a preferential extraction in the tissues that constitutionally express CB2 cannabinoid receptor. The results obtained indicate [ 18 F]CB91 as a possible candidate marker of CB2 cannabinoid receptor distribution. This study would open the way to further validation of this tracer for assessing pathologies for which the expression of this receptor is modified.